Spatial and ontogenetic variability in the diet and trophic ecology of two co-occurring catsharks (Scyliorhinidae) off South Africa. Issue 4 (1st October 2020) - van der Heever, GM; van der Lingen, CD; Leslie, RW; Gibbons, MJ
Abstract : The Izak catshark Holohalaelurus regani and the yellow-spotted catshark Scyliorhinus capensis both occur over the continental shelf around South Africa and are often caught together as bycatch in demersal trawls. Yet our understanding of their diet is fragmented, which makes determination of their place in ecosystem models difficult. Using material collected along the coastline and at a variety of depths, we analysed the diet and assessed the trophic ecology of different size classes of each species, using analyses of stomach contents and stable isotopes. The most important prey items consumed by both species were crustaceans, cephalopods and teleosts. Higher-trophic-level prey were more important for H. regani than for S. capensis, and these prey were also more common in the diet of each species on the west coast than on the south coast. Differences in the prey species consumed, compared by coast, size class and depth, were also detected, with the catshark species feeding on the (presumed) most-abundant prey on each coast. Individual catsharks consumed larger, higher-trophic-level prey items with increasing size and depth. Dietary differences were also reflected in the stable isotopes: generally higher δ 15 N values were noted from samples on the west coast than on the south coast; a significant interspecific difference in δ 15 N values was detected; and δ 15 N values increased with increasing size in both species. The present study provides a multidisciplinary framework for a better understanding of the diet and trophic ecology of these catshark species and emphasises the important structuring role (through food-web effects) that these fish play in benthic communities off South Africa's coast.